UPAYA SIMBOLIK PENGAWETAN WACANA ANTI-KOMUNIS : Analisis Wacana Kritis atas Majalah Matan terbitan Muhammadiyah Jawa Timur - , RADIUS SETIYAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The discourse of communism in Indonesia is closely related to the tragedies involving the Communist Party of Indonesia (PKI). Meaning of the ideology of communism has become a symbolic fight arena. PKI as victims or as perpetrators of the massacre into a debate that continues to this day. The assumption has implications on the meaning of \\"communism as an ideology\\" in Indonesia. That to this day is still a scourge of communism for most of society is a reality. Although Suharto has fallen, the effort to preserve the anti-communist discourse into a phenomenon in Indonesia. This research study focuses on how Matan Magazine in East Java Magazine seeks to preserve the anti-communist discourse. The goal is to get the power to produce and show the view of the world's most recognized, most assumed to be true, which has legitimacy. Symbolic preservation efforts on the anti-communist discourse conducted with meconaisance strategy, namely eufimisasi, sensorisasi and implicature. In addition, Matan shows some old wells in an effort to preserve the discourse. Through the method of critical discourse analysis, this study showed that up to now the Muhammadiyah Islamic organization which active in reproducing the anti-communist discourse in Indonesia. This is done through images and written narrative in which the magazine wanted to instill a spirit of cruelty, crime and other things are bad on the PKI or communism. In addition to writing narrative and productive sites in reproducing discourse, there are still many characters that way figures has not shifted at all on the hegemony of the regime. Way of thinking that tends to stagnate on the anti-communist discourse can be correlated with the idea of the purification in Muhammadiyah. Keywords: Symbolic efforts, anti-Communist Discourse, Matan